Colombia’s COIN Strategy: Population-Centric Theory in Asymmetric Conflict - Rina Mega Zerlina (Universitas Airlangga, 2026)
This study argues that the Colombian government’s counterinsurgency (COIN) strategy against the FARC exemplifies both the potential and limitations of David Galula’s population-centric COIN theory in the context of asymmetric warfare. Galula emphasizes that successful COIN is 80% political and only 20% military, prioritizing civilian support through “clear, hold, build” operations. This study employs a qualitative case study method using David Galula’s counterinsurgency (COIN) theory as the main analytical framework. Data are drawn from secondary sources such as academic literature, policy documents, and international reports, analyzed through a theory-driven content analysis. Colombia adopted this framework by integrating military offensives with state-building, rural development, and reintegration programs to win the “hearts and minds” of the population. While military efforts under Plan Colombia significantly weakened the FARC’s operational capacity, widespread human rights violations, particularly the “false positives” scandal, undermined public trust and deviated from Galula’s principle of civilian protection. This case reveals the dilemma of applying COIN in asymmetric conflicts, where insurgents exploit ideological and tactical advantages, while states must uphold legitimacy. Ultimately, the Colombian experience confirms that lasting peace necessitates more than force; it requires justice, trust, and a sustained state presence. Keywords: Asymmetric Warfare; Counterinsurgency (COIN); David Galula; FARC; Colombia.